Do slotting allowances harm retail competition? - Øystein Foros; Hans Jarle Kind (Center for Economic Studies and ifo Institute (CESifo), 2006)
Slotting allowances are fees paid by manufacturers to get access to retailers' shelf space. Both in the USA and Europe, the use of slotting allowances has attracted attention in the general press as well as among policy makers and economists. One school of thought claims that slotting allowances are efficiency enhancing, while another school of thought maintains that slotting allowances are used in an anti-competitive manner. In this paper, we argue that this controversy is partially caused by inadequate assumptions of how the retail market is structured and organized. Using a formal model, we show that there are good reasons to expect anti-competitive effects of slotting allowances. We further point out that competition authorities tend to use an unsatisfactory basis for comparison when analyzing welfare consequences of slotting allowances.
Keywords: L13; L42; L81; 330; Einzelhandel; Verkaufsförderung; Lieferanten-Kunden-Beziehung; Preiswettbewerb; Konzentrationspolitik; Theorie